OUTCOMES AMONG PATIENTS WITH SEX CORD STROMAL TUMOUR OF OVARY: EXPERIENCE FROM PAKISTAN - Sarwar, Sohail; Siddiqui, Neelam; Ather, Sohail; Hannan, Abdul; Syed, Amir Ali; Zafar, Waleed (Journal of Ayub Medical College Abbottabad, 2014)
Background: Ovarian sex cord-stromal tumours (SCST) are relatively uncommon neoplasms that account for approximately 5-7% of all primary ovarian tumours. The aim was to report experience with sex cord stromal tumours (SCST) of ovary in a low and middle income country. Methods: Clinical records of 56 patients with histopathologically-established SCST of ovary admitted to a tertiary care cancer hospital in Pakistan between April 1995 and December 2011 were reviewed. Results: Median age at presentation was 41 years (Range 4-77). Forty one (73%) patients were premenopausal and 15 (26.8%) were postmenopausal. The most common presenting complaint was abdominal pain (28.1%). Thirty seven patients (66%) had stage-I, 2 had stage II and III each, and 15 (26.8%) had stage IV disease. Five years survival in patients with early stage (stages I & II) was 91% while in those in the late stage (III & IV) was 84% (p=0.79). Histopathologically, 49 patients (85.7%) had Granulosa cell tumour, and 7 (12.5%) had Sertoli Lyedig cell tumour. CA-125 was high only in 8 patients (14.3%). Adjuvant chemotherapy was given in 16 (28.6%). Thirty six (64%) were disease free at last follow up, 10 (18%) succumbed to disease and 10 (18%) were alive with disease. On univariate and multivariate analyses, late stage at presentation was the sole factor significantly associated with mortality. Conclusion: Ovarian sex cord-stromal tumours of ovary are relatively uncommon malignancies with good prognosis if diagnosed early and treated adequately. Survival in our study was comparable to those reported elsewhere. Among various factors, late stage of tumour at presentation was found to be the only factor significantly associated with mortality. Keywords: Sex Cord Stromal Tumour, Ovary, Granulosa cell tumour, Prognosis